Regulatory Framework of Fortified Foods and Dietary Supplements for Athletes: An Interpretive Approach - Susana Menal-Puey (MDPI AG, 2021)
A varied and well-planned diet can meet the nutritional needs of an athlete; however, in certain cases, it could be advisable to increase the intake of some vitamins, minerals or other components through the controlled intake of fortified foods or dietary supplements. In the European Union, a high number of sport foods and supplements are marketed; athletes could at times consume them indiscriminately or even choose products that have not been evaluated and approved by scientific evidence. In this sense, it is necessary to know and interpret the specific regulations for these products in order to make adequate use of them. The aim of this manuscript is to describe the current status of the European regulatory framework, focusing on: (1) regulation of the marketing and labelling of both fortified foods and supplements; (2) regulation of the use of substances used as ingredients in fortified foods; and (3) regulation of nutritional claims and/or health properties associated with nutrients, ingredients and other related substances. This review can facilitate knowledgeable decision making by sports nutrition professionals in order to counsel or manage adequate food choices as well as help consumers make better-informed food decisions. Other experts, such as producers who ensure food safety, might also be interested in this review.